PENINGKATAN DAYA TAHAN BAMBU DENGAN PROSES PENGASAPAN UNTUK BAHAN BAKU KERAJINAN - Arsad, Effendi (Kementerian Perindustrian, 2014)
Bamboo in South Kalimantan has not been used optimally, it is because bamboo susceptible organisms, including termites and powder. Research durability of bamboo with a curing process for raw materials craft has been done. This study aims to improve the durability of bamboo as raw material craft. The type of raw materials used are bamboo lear (Gigantochloa smear Kurz) and Bamboo betung (Gigantochloa atter). Old fumigation 5 days, 10 days and 15 days. Long trial against termites feed bamboo strips 10 days, 20 days and 30 days. Long curing time can improve the durability of bamboo strips against destructive organisms. 30 days storage of small attacks against the bamboo strips. Curing process can be used as a way of preservation of bamboo as raw material for handicrafts. Keywords: bamboo, fumigation, durability, organisms